2016
DOI: 10.4103/0253-7176.194909
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Young Suicide Attempt Survivors in a Tertiary Care Hospital in Puducherry

Abstract: Context:Puducherry has the highest suicide prevalence rate in India by 2014, predominantly among the 14–30 years age group.Aims:The aim of the present study is to study the characteristics of adolescent and youth suicide attempters in Puducherry and measure the suicide intent.Settings and Design:An observational study of 6 months duration was conducted in the Department of Psychiatry, at Sri Manakula Vinayagar Medical College and Hospital, Puducherry, India.Materials and Methods:Modified version of World Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Four of the twenty (20%) studies included, focused exclusively on paediatric populations [12,13,14], and eight (40%) had a mixed demographic which included those under the age of eighteen as well as adults. Of these Lingeswaran et al described a population with age range of ten to thirty years [15]; Mitrev reported an age range of fifteen to over sixty years [16], and Ghimire et al described a population of two hundred presentations to an ED in Nepal that ranged in age from fifteen to fifty-five years (77% of whom were aged under 34 years) [17]; McCauley et al described a population aged between 10 and 60 years in an ED in a hospital in rural Ireland, close to half of the sample were aged less than thirty [18]; Galgali et al reported a mean age of 25 (SD = 8.1) in their sample, without describing a range [19]; Zarghami et al reported an average age of 27 years (SD = 13.5), again without specifying the age range [20]; Abumadani et al report an patients in Saudi Arabia aged 13–74 [21] and Wai et al focused on a young adult/adolescent population all aged under 21 [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the twenty (20%) studies included, focused exclusively on paediatric populations [12,13,14], and eight (40%) had a mixed demographic which included those under the age of eighteen as well as adults. Of these Lingeswaran et al described a population with age range of ten to thirty years [15]; Mitrev reported an age range of fifteen to over sixty years [16], and Ghimire et al described a population of two hundred presentations to an ED in Nepal that ranged in age from fifteen to fifty-five years (77% of whom were aged under 34 years) [17]; McCauley et al described a population aged between 10 and 60 years in an ED in a hospital in rural Ireland, close to half of the sample were aged less than thirty [18]; Galgali et al reported a mean age of 25 (SD = 8.1) in their sample, without describing a range [19]; Zarghami et al reported an average age of 27 years (SD = 13.5), again without specifying the age range [20]; Abumadani et al report an patients in Saudi Arabia aged 13–74 [21] and Wai et al focused on a young adult/adolescent population all aged under 21 [22].…”
Section: Resultsmentioning
confidence: 99%
“…Lingeswaren et al reported that 100% of the people seen with self-poisoning had a diagnosis of AD. It is not clear from the study whether a diagnosis of AD was a selection criterion or whether all patients who presented during the timeframe of the studies happened to have a diagnosis of AD [15].…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 29 31 32 34 35 36 ] A few studies have found adjustment disorder to be the most common disorder. [ 37 38 39 40 ] Two studies have found personality disorders, mainly emotionally unstable personality disorder to be the most common psychiatric diagnosis. [ 27 41 ] Two studies found the most common psychiatric diagnosis to be alcohol dependence syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in rate in later adolescence may be due to greater psychopathology, more cognitive ability to plan and act, more autonomy, and less supervision. [ 26 ] Majority attempters were females, nearly, all studies on adolescent suicide attempts have reported more representation of females[ 26 27 28 29 ] Although in the traditional Indian culture, women enjoy a more protected role, the changing expectations, and workforce participation, the female sex also experience a concurrent rise in role conflicts and psychosocial stressors. The hostile environment in families, preexisting personality problems, and mental illness could precipitate suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were comparable to these earlier studies where similar findings were found. [ 25 29 ] The reason for this variation in findings can be attributed to the fact that the data has been collected from an urban setting where usage and possessing of insecticides at home is not as common as in rural settings. Still, this cause amounts to the second most common cause in our study.…”
Section: Discussionmentioning
confidence: 99%